SEASONAL LABOUR MARKET RIGIDITIES: IMPACT ON FARM EMPLOYMENT AND WAGES IN NIGERIA - Olakojo, Solomon Abayomi; - Fact Sheet:, Africa (Economics of Agriculture, 2016)
This study investigates the sensitivity of wages and employment in the agricultural sector to seasonal demand and productivity conditions facing Nigerian farmers. It develops a data consistent analytical model that incorporates seasonality in farm employment and wages. This was tested empirically using the Living Standards Measurement StudyIntegrated Surveys on Agriculture (LSMS-ISA) for Nigeria for the year 2012/2013. The study fnds that, during harvest, farmers are signifcantly less likely to employ male labourers and pay them lesser wages. Contrarily, female labourers are more likely to be employed and paid higher wages in harvest. The decline in male employment and increase in female employment during harvest is stronger for medium (-0.15%) and large scale farmers (0.22%), respectively. The decline in male wages and increase in female wages during harvest is stronger for large (-0.25%) and low scale farmers (0.22%), respectively. This study recommends policy options to minimize undesired employment effect of seasonality.